African separatists: heresy, schism or protest movement? - Hinchliff, Peter (Studies in church history, 1972)
Africa has never been an absolutely dark continent to those who live elsewhere. From the days of the Phoenician traders of Carthage to the Afro-Arab mercantile empires of the fifteenth century Africa was always a source of what more literate peoples wanted. Long before modern Europeans began to explore the continent others had been there and taken their literary skills with them. In 1857 Richard Burton - the real Richard Burton - went on a journey to find the ‘reputed great Lake Tanganyika’ for the Royal Geographical Society. One hundred and thirty-four days’ journey into the interior he was the guest of an Arab dealer in slaves and ivory, of whom he said, ‘ He had read much, and, like an oriental, for improvement, not only for amusement: he had a wonderful memory, fine perceptions and passing power of language’. Arabic and Islamic culture penetrated into, and made a lasting impression on, many parts of Africa. Reading and writing sometimes accompanied this penetration and there are fascinating traces of attempts to reduce African languages to writing in Arabic script. Nevertheless, writing a history even of modern Africa requires a very different technique from that which is needed to write a history of Europe in the same period because it is far less concerned with documents.